The mighty Mars rovers : the incredible adventures of Spirit and Opportunity - Rusch, Elizabeth (Houghton Mifflin Books for Children, 2012)
The story of the two robot vehicles, Spirit and Opportunity, that were sent to explore Mars, lasting far past their projected lives of three months and sending back invaluable images of the environmentally hostile planet.